Cities under Capitalism: Surveillance, Displacement, and the Technology of Homogenisation - Ökten, Burcu Balaban; Habbaz, Dima (İstanbul Üniversitesi, 2025)
This article explores how capitalism, combined with technological developments, reshapes urban identity and contributes to the homogenisation of cities. This article examines the impact of economic and technological forces on the social and spatial character of contemporary urban environments. The article adopts a critical literature review combined with a synthesis of three cases: historical capitalism, urban identity/homogenisation, and technological capitalism. The original contribution is to articulate homogenisation across physical, symbolic, and data layers and to translate this into design and governance. The results highlight that while earlier forms of capitalism transformed cities through material produc tion and largescale redevelopment, contemporary capitalism operates through digital infrastructures, surveillance systems, and the circulation of images and data. This shift has intensified spatial homogeni sation, weakening the unique identities of urban areas and challenging the continuity of community life. The article argues that architects and planners hold a crucial responsibility in addressing these dynamics. By acknowledging the technological dimension of urban transformation, they can critically engage with capitalist pressures and develop inclusive strategies that preserve diversity while using technology in socially responsible ways. Ultimately, the study emphasises the need for alternative approaches that safeguard identity, community, and equity in the rapidly changing urban landscape.
Keywords: Architectural Design; Mimari Tasarım [EN] Architecture (Other); Mimarlık (Diğer)